The Role of Work Motivation as a Mediating Influence Between Compensation and Procedural Justice on Job Satisfaction - Mawaddah, Apriani; Darmawan, Akhmad; Purnadi, Purnadi; Utami, Restu Frida (Asian Journal of Management Analytics, 2025)
This study analyzes the effect of compensation and procedural justice on job satisfaction with work motivation as a mediating variable in production employees of PT Royal Korindah Purbalingga. This research uses a quantitative approach with stratified random sampling method. The population amounted to 474 employees, the research sample amounted to 106 employees. Data were analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The results showed that compensation and procedural justice had a positive and significant effect on job satisfaction and work motivation, work motivation had no significant effect on job satisfaction, work motivation did not mediate the relationship between compensation and procedural justice on job satisfaction. These findings fill the theoretical gap by confirming that the effect of compensation and procedural justice on job satisfaction is not through the mediation path of work motivation.